Is it Essential to Put a Drain in Patients with Cholecystectomy? - Mohialdeen , Fadhil A (Diyala Journal of Medicine, 2019)
Background: The gallbladder is an important organ, but is not essential for life. Therefore, the standard treatment for symptomatic patients who suffer from gallstones has been to surgically remove the gallbladder and gallstones, Cholecystectomy, which is one of the most commonly, performed surgical procedures. Aim: Fifty patients undergoing cholecystectomy had either no drain and another fifty had a narrow bore suction drain or an open corrugated drain. More complications were seen in the group with drain compared to the other group without drain. Materials and Methods: This study was performed in the Shorsh General Hospital in sulaimaniyah from October 2010 to October 2011. The aim of this study was to determine whether drains influenced the Patient comfortably, discharge of the patient from hospital, appearing of hernia after operation, intestinal obstruction, and the risk of drain site infection following cholecystectomy, and if these had any affect on complications. Results: According to our data there was a statistical significance between two methods of surgical operation of gall bladder in the criteria (patient comfortably, discharge of patient from hospital, appearing hernia after operation and risk of drain site infection (p value < 0.05), but there was no any statistical significance for intestinal obstruction (p value > 0.05). Conclusion: We suggest that drainage in cholecystectomy is unnecessary and, if an open drain is used, it may be potentially dangerous.